Analysis of epidemiological and operational indicators of cutaneous leishmaniasis in Teófilo Otoni – MG (Research, Society and Development, 2023)
The present study was conducted in the municipality of Teófilo Otoni, which stands out as an important area of LT occurrence with a detection rate of 24.2%, being classified as a high-risk area.The main objective of this study was to calculate and analyze the epidemiological and operational indicators in the period from 2016 to 2021 in Teófilo Otoni- Minas Gerais. The epidemiological and operational indicators were evaluated through the use of secondary data extracted from the SINAN database, which also provided the establishment of the epidemiological profile of the grievance and the historical series of distribution of cases. The indicators analyzed were: absolute number of cases, general coefficient of detection of cases of LT, proportion of cases of LT in the age group under 10 years, proportion of cases of LT in the age group 65 years or older, proportion of cases of LT in males, proportion of cases of LT confirmed by laboratory criteria and proportion of cases of LT that evolved to clinical cure. The results showed the characterization of cases and the evolution of indicators in the historical series year by year and in triennials. It is noteworthy that there were changes in the results of the indicators over time, especially in laboratory diagnosis, direct parasitological examination, which is attributed to service restructuring actions and educational activities carried out in the municipality that may have impacted on the improvement of indicators.